Elevated fetal haemoglobin levels are associated with decreased incidence of retinopathy in adults with sickle cell disease. (12th November 2018) - Mian, Umar K.; Tang, Joyce; Allende, Ana P. M.; Heo, Moonseong; Bernstein, Nicole; Vattappally, Leena; Schoenfeld, Daniel; Minniti, Caterina P.
Summary: Among the many vascular complications of sickle cell disease (SCD), retinopathy is the most prevalent and represents a leading cause of blindness. Hydroxycarbamide therapy ameliorates many symptoms of SCD, and high fetal haemoglobin (HbF) levels have been shown to protect against the development of retinopathy in children with HbSS. Its effect on adults with SCD, who are at a much higher risk of developing retinopathy, has not been studied. We aimed to investigate the effect of hydroxycarbamide use and HbF level on sickle cell retinopathy development in adults. We performed a retrospective cross‐sectional study and collected demographics, comorbidities, and ocular and haematological data from 300 adult sickle cell subjects examined at the Henkind Eye Institute at Montefiore Medical Center during a 5‐year period, from October 2012 to November 2017. The cohort was comprised mainly of Black and Hispanic subjects with all SCD genotypes, aged 18–71 years. Results show that in HbSS patients treated with hydroxycarbamide, those with retinopathy had significantly lower HbF levels compared to patients without retinopathy ( P  = 0·018). Our study identified the optimal HbF cut‐off point for retinopathy protection to be 14·87%. Thus, a HbF level of 15% appears to be the threshold above which the odds for developing retinopathy in SS patients are reduced by 50%.